2018
DOI: 10.3389/fenvs.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction of Natural Fe(III) Minerals; Toward the Sustainable Production of Functional Magnetic Nanoparticles

Abstract: The microbial synthesis of biominerals offers a potentially sustainable green solution for the production of a wide range of industrially relevant functional nanomaterials. Metal-reducing bacteria are of particular relevance, as they can enzymatically reduce a wide spectrum of high oxidation state metals and metalloids, forming cell-templated nanomagnets, catalysts, remediation agents, and quantum dots. Although these bioprocesses have been shown to be both scalable and tunable (with respect to particle size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…In anaerobic environments, dissimilatory iron-reducing bacteria, such as Shewanella oneidensis, Geobacter sulfurreducens, and so forth, can utilize anaerobic respiration to produce electrons and then transfer them to Fe­(III) in the environmental matrices through direct contact or electron shuttles, leading to the generation of Fe­(II). This is an important process which affects the redox speciation of iron in groundwater, soils, and sediments. Previous studies have tried to elucidate the mechanisms of electron transfer between bacteria and minerals, to clarify the resulting effects on the cycles of carbon, nitrogen, and sulfur in terrestrial and aquatic environments, and to explore its applications in contamination remediation. , When converting to an aerobic environment, Fe­(II) is easily oxidized to Fe­(III), accompanied by the spontaneous production of abundant • OH. , Recent studies have been conducted to investigate the production of • OH through chemical oxidation of Fe­(II)-bearing clays, , sediments , and ferrous minerals, and its effects on the oxidation of contaminants in the environment. ,,, Particularly, the research by Yuan et al revealed the one-electron transfer mechanism of • OH production derived from oxygenation of chemically reduced structural Fe­(II) in nontronite and pointed out that O 2 •– and H 2 O 2 were involved in the generation of • OH. Zeng et al .…”
Section: Introductionmentioning
confidence: 99%
“…In anaerobic environments, dissimilatory iron-reducing bacteria, such as Shewanella oneidensis, Geobacter sulfurreducens, and so forth, can utilize anaerobic respiration to produce electrons and then transfer them to Fe­(III) in the environmental matrices through direct contact or electron shuttles, leading to the generation of Fe­(II). This is an important process which affects the redox speciation of iron in groundwater, soils, and sediments. Previous studies have tried to elucidate the mechanisms of electron transfer between bacteria and minerals, to clarify the resulting effects on the cycles of carbon, nitrogen, and sulfur in terrestrial and aquatic environments, and to explore its applications in contamination remediation. , When converting to an aerobic environment, Fe­(II) is easily oxidized to Fe­(III), accompanied by the spontaneous production of abundant • OH. , Recent studies have been conducted to investigate the production of • OH through chemical oxidation of Fe­(II)-bearing clays, , sediments , and ferrous minerals, and its effects on the oxidation of contaminants in the environment. ,,, Particularly, the research by Yuan et al revealed the one-electron transfer mechanism of • OH production derived from oxygenation of chemically reduced structural Fe­(II) in nontronite and pointed out that O 2 •– and H 2 O 2 were involved in the generation of • OH. Zeng et al .…”
Section: Introductionmentioning
confidence: 99%
“…Production of BNM from waste iron oxides could further enhance the green credentials of this CuAAC catalyst synthesis method. 32 The ability of the BNM to act as both the initial recovery agent and subsequent support for the Cu improves the atom efficiency of the process and reduces the number of steps required for catalyst synthesis. Simple magnetic separation and recovery of the Cu lees BNM following the CuAAC adds to the benefits of heterogeneous catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lovley et al, 1987;Lloyd, 2003;Weber et al, 2006;Newsome et al, 2018;Kappler et al, 2021) releasing aqueous Fe(II) (Lloyd, 2003;Lovley et al, 2004). Dissimilatory metal-reducing bacteria can also liberate trace metals such as Cr, Ni and Co associated within oxidised mineral phases, such as ferrihydrite (Lee et al, 2001;Lloyd, 2003;Zhang and Cheng, 2007;Joshi et al, 2018). In the absence of an electron shuttle, G. sulfurreducens preferentially performs this electron transfer process via a direct contact mechanism, mediated by outer membrane multiheme c-type cytochromes localised to the cell surface (Lloyd, 2003;Lovley et al, 2004;MacDonald et al, 2011;Malvankar et al, 2011;Levar et al, 2016;Newsome et al, 2018) with extracellular pili also recently implicated in electron transfer (Lovley and Walker, 2019).…”
Section: Introductionmentioning
confidence: 99%